Personal Finance Management in the Digital Age; Opportunities, Challenges, and Strategies for Indonesians - Ariselip; Tarigan , Heskeyel Pranata (Journal of Accounting and Management, 2024)
Personal financial management is a vital skill to manage income, expenses, savings, and investments to achieve financial well-being. In the digital era, the emergence of financial technology (fintech) brings new opportunities as well as challenges for Indonesian society. This article examines the theoretical basis of personal financial management, the level of financial literacy of the community, the role of fintech, and the challenges that arise. Through a literature study and case study approach, this article outlines effective financial management strategies and recommendations to improve the economic well-being of the community in a sustainable manner. This study also highlights the role of digital financial education and regulation in creating a healthy financial ecosystem.